Politik, Agama, Budaya dan Pengaruhnya Terhadap Legislasi dan Penerapan Nilai-Nilai Hak Asasi Manusia di Indonesia - Ali Mansur; Afwan Faizin (SALAM: Jurnal Sosial dan Budaya Syar-i, 2021)
This article aims to describe the influence of religion and culture in the application of human rights values, as well as the dynamics of its acceptance of legislation in Indonesia. Human rights thoughts and struggles had developed in Indonesia prior to the Universal Declaration of Human Rights in 1948. The embryo of this awareness has flourished in the midst of the bad conditions experienced by the Indonesian people due to colonialism. Precisely since the momentum of the birth of the Budi Utomo movement in 1908, it has laid the foundation for the struggle against the application of human rights values and continues to be a snowball effect in the next period and culminated in the proclamation of Indonesia's independence as a sovereign state on August 17, 1945. In historical records, at the moment of independence, it was the first time Indonesia had a written document containing human rights values, in this case Pancasila and the 1945 Constitution (UUD 1945). However, despite being independent, the struggle for the application of human rights values does not mean it will run smoothly without obstacles, The dynamics of socio-political life in Indonesia illustrates how the ups and downs of the application of human rights values in Indonesia, such as the influence of politics, religion and culture. To get the results, the researchers used a qualitative research method with an amperical normative approach.Keywords : Legislation, Human Rights values, politics, religion, cultur. Abstrak:Artikel ini bertujuan memaparkan pengaruh agama dan budaya dalam penerapan nilai-nilai HAM, serta pasang surut penerimaannya pada legislasi perundang-undangan yang berlaku di Indonesia. Pemikiran dan perjuangan Hak Asasi Manusia telah hidup dan berkembang di Indonesia jauh sebelum deklarasi Universal Hak Asasi Manusia pada tahun 1948. Cikal bakal kesadaran tersebut telah tumbuh subur di tengah kondisi buruk yang dialami masyarakat Indonesia akibat penjajahan yang berkepanjangan. Tepatnya sejak momentum kelahiran pergerakan Budi Utomo di tahun 1908, telah meletakan pondasi perjuangan terhadap penerapan nilai HAM dilakukan dan terus menjadi efek bola salju pada masa masa selanjutnya dan membuahkan hasil saat proklamasi kemerdekaan Indonesia sebagai negara yang berdaulat pada 17 Agustus 1945. Dalam catatan sejarah, dengan momentum kemerdekan ini pula Indonesia pertama kali memiliki dokumen tertulis yang mengandung nilai-nilai HAM dalam hal ini Pancasila dan Undang-Undang Dasar 1945. Namun demikian, meskipun telah memasuki alam kemerdekaan, perjuangan penerapan nilai-nilai HAM bukan berarti mulus tanpa hambatan. Dinamika dan perkembangan kehidupan social politik di Indonesia memberikan gambaran bagaimana pasang surut penerapan HAM di Indonesia, mulai dari pengaruh politik, agama serta budaya.  Dalam penelitian ini, peneliti menggunakan metode penelitian kualitatif dengan pendekatan noematif empiris.Kata kunci : Legislasi, Nilai-Nilai HAM, Politik, Agama, Budaya.